Confession and Community in Seventeenth-Century France : Catholic and Protestant Coexistence in Aquitaine - Hanlon, Gregory (University of Pennsylvania Press, 2016)
Examines the tolerance between Catholics and Protestants in a period when vicious sectarian strife was the rule of the day. Tolerance here means more than mere coexistence but a daily interaction between people without regard for their faith.